Effects of copper on chlorophyll, proline, protein and abscisic acid level of sunflower (Helianthus annuus L.) seedlings - Zengin, Fikriye Kirbag; Kirbag, Sevda (Triveni Enterprises, 2007)
The effect of copperchloride (CuCl2) on the level of chlorophyll (a+b), proline, protein and abscisic acid in sunflower (Helianthus annuus L.) seedlings were investigated. Control and copper treated (0.4, 0.5 and 0.6 mM) seedlings were grown for ten days in Hoagland solution. Abscisic acid content was determined in root, shoot and leaf tissues of seedlings by HPLC, Copper stress caused significant increase of the abscisic acid contents in roots, shoots and leaves of seedlings. The increase was dependent on the copper salt concentration. Enhanced accumulation of proline in the leaves of seedlings exposed to copper was determined, as well as a decrease of chlorophyll (a+b) and total protein (p < 0.05 or p < 0.01). It was observed that the level of chlorophyll (a+b) and total protein (p < 0.05 or p < 0.01) remarkably decreased as copper concentration increased to 0.6 mM, although the levels of proline and abscisic acid in the leaves of plants were increased - a dose-depended behavior. The same trends were also observed with the level of abscisic acid of stems and roots. Copper has dose-depended effects on chlorophyll, proline, protein and abscisic acid level of sunflower (Helianthus annuus L.) seedlings. Thus, we assumed that copper levels increase above some critical points seedling growth get negative effects. This assumption is in line with previous findings.
Keywords: sunflower seedling; copper; abscisic acid; chlorophyll; protein; proline